Mythology, Pilgrimage, and Planning: A Data-Driven Study of Religious Tourism and Development in Naimisharanya, Uttar Pradesh (International Journal of Food and Nutritional Sciences, 2023)
Naimisharanya, located in the Sitapur district of Uttar Pradesh, is one of India's most sacred pilgrimage sites, deeply rooted in mythological and spiritual narratives found in the Mahabharata, Ramayana, and various Puranas. In recent years, this holy town has come under the spotlight through the Government of India's Swadesh Darshan 2.0 initiative, which aims to transform heritage and spiritual destinations into hubs of sustainable tourism. This research paper offers a comprehensive examination of Naimisharanya’s religious significance, socio-economic profile, tourism trends, and infrastructural development, using primary data from the Draft Destination Master Plan (2023) along with scholarly literature. The study analyses critical indicators such as tourist footfall, demographic patterns, literacy rates, and workforce participation. It also presents a phased investment strategy worth ₹754 crore proposed under the Master Plan and visualizes these insights through relevant tables and graphs. Beyond quantitative data, the paper evaluates pressing challenges such as poor sanitation, informal encroachments, and the lack of digital visitor infrastructure. The discussion highlights how religious tourism can serve as a vehicle for inclusive rural development when supported by sound governance, cultural sensitivity, and community participation. This research positions Naimisharanya as a living example of India’s sacred geography and advocates for a development model that balances spiritual preservation with modern-day planning imperatives.